2018
DOI: 10.3892/etm.2018.6028
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effects of bee venom on some metabolic and antioxidant parameters associated with HFD‑induced non‑alcoholic fatty liver in rats

Abstract: Abstract. The present study was designed to investigate the therapeutic effects of bee venom (BV) on high-fat diet (HFD)-induced non-alcoholic fatty liver (NAFL) in rats at different levels. Histological manifestations, hepatic lipid content, liver function tests, glucose homeostasis, lipid abnormalities, adipocytokines, lipid peroxidation, disturbed glutathione and antioxidant enzymes systems and dysregulation of Nrf2 transcription factor were assessed. In the present study, the NAFL rats were subcutaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
5
15
0
Order By: Relevance
“…However, these changes were markedly attenuated by the administration of bee venom. These findings are in good agreement with recent studies showing the anti-oxidative effects of bee venom in an animal model of non-alcoholic fatty liver disease [ 29 ] and Parkinson’s disease [ 30 ]. In addition, bee venom decreased LPS-induced generation of reactive oxygen species in bovine mammary epithelial cells [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, these changes were markedly attenuated by the administration of bee venom. These findings are in good agreement with recent studies showing the anti-oxidative effects of bee venom in an animal model of non-alcoholic fatty liver disease [ 29 ] and Parkinson’s disease [ 30 ]. In addition, bee venom decreased LPS-induced generation of reactive oxygen species in bovine mammary epithelial cells [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…The lipid profile values of serum TG, total lipids, total cholesterol, LDL-C, and HDL-C were completely normalized by BV treatment in addition to reduced body weight. These results are in agreement with those of Hanafi et al [26]. There was a causative parallel reduction in hepatic contents of both SREBP1c and SREBP2.…”
Section: Discussionsupporting
confidence: 94%
“…Group 3: Rats received 10% fructose in drinking water and BV, dissolved in saline, (0.1 mg/kg, i.p.) 3 times per week [25, 26] during the last 2 weeks of the experiment (7th and 8th weeks).…”
Section: Methodsmentioning
confidence: 99%
“…Our results are in accordance with those reported by Hanafi et al, who showed that the activities of serum transaminases, AST, ALT, and GGT, were significantly increased in NAFLD rats. Also, NAFLD rats demonstrated higher bilirubin values [31]. These significant abnormalities of liver function tests revealed a state of hepatocytes inflammation and slightly damage as indicated by the histological results.…”
Section: Discussionmentioning
confidence: 72%